THE ALGORITHMIC ORDER: CONTEMPORARY INTERNATIONAL RELATIONS IN THE DIGITAL AGE - Dr. Taha Shabbir; Dr. Usman Farooq; Dr. Sobia Usman (Policy Journal of Social Science Review, 2025)
This study investigates the transformation of contemporary international relations in the digital age, with particular emphasis on the role of algorithms and artificial intelligence (AI) in reshaping global power dynamics. Digital infrastructures—ranging from social media platforms to surveillance systems—have become central to the conduct of diplomacy, security, and governance. AI-driven technologies such as predictive analytics, automated decision-making, and autonomous weapons not only amplify state capabilities but also create new vulnerabilities, raising questions about ethics, accountability, and sovereignty. Drawing on interdisciplinary scholarship in international relations, digital governance, and security studies, this research develops an analytical framework that situates algorithms and AI as structural forces comparable to material power and institutional norms. The findings suggest that digital platforms and AI systems are simultaneously tools of influence, instruments of competition, and contested arenas where states and non-state actors negotiate legitimacy, authority, and control. Keywords: Internet, Data, International Relations, Political Science, Global Media